Reforming Taxpayer Identification: A Literature Study on the NIK-NPWP Synchronization Framework in Indonesia - Tofan, Ali (International Journal of Pertapsi, 2025)
This study investigates the integration of the Population Identification Number (NIK) as the Taxpayer Identification Number (NPWP) in Indonesia's tax administration system. The research examines its impact on taxpayer compliance, administrative efficiency, and data accuracy. Results indicate that the synchronization of NIK and NPWP significantly enhances compliance by addressing information asymmetry, improving data reliability, and simplifying administrative processes. However, challenges such as data mismatches, limited technological infrastructure, and low public awareness persist, hindering the full potential of this initiative. The study underscores the importance of adopting advanced technologies like blockchain and implementing targeted educational programs and policy interventions to overcome these barriers. This integration is identified as a pivotal step in fostering a transparent and efficient tax ecosystem in Indonesia. The findings contribute to the discourse on tax system modernization and offer actionable insights for enhancing governance and compliance in emerging economies.